Microorganismos Fijadores De Nitrógeno Y Su Acción Complementaria A La Fertilización Química En El Cultivos De Coffea arabica L. - Danilo Santana-Aragone; Eduardo Colina-Navarrete; Carlos Castro-Arteaga; Dalton Cadena-Piedrahita; Arianna Sotomayor-Morán; Edgar Galarza-Centeno; Marlon López-Villacrés (European Scientific Journal, ESJ, 2017)
The objective of this work was to evaluate the effect of nitrogen's fixers complementaries to the chemical fertilization in the coffe groing. Ten treatments were used and three repetitions in plots of twenty-five plants, which were distributed in a complete blocks design at random. For the evaluation of averages were used the Tukey test at 95% confidence. During the cycle of the crop was evaluated: plant height, stalk diameter per plant, number of branches per plant, number of grains per plant, weight of 100 grains, yield per hectare of gold coffee and an economic analysis of the treatments. As a result of the experiment, it was noticed that the biofertilizers impacted on the development and performance of coffee cultivation, there was also an increase performance with higher values to the witness. The highest performance was submitted with the application of Micro-Asp (Azospirillium brsilense) in a dose of 6 l/ha in combination with a program of fertilization (160 kg N, 60 kg P, 75 kg K, 30 kg S, 20 kg Mg, 0.4 kg B, 0.2 kg Zn) based on the analysis of soil, achieving 1118.75 kg/ha of gold coffee, the same that is 4.29 times greater than the witness (260,7 kg/ha of gold coffee).